Bio Removal of Copper (Cu+2) and Cobalt (Co+2) by Chlorella Vulgaris From Aqueous Solutions - Hala Faez Abdul-Hadi Al-Jewahery, Jassim Mohammed Salman (Scientific Trends, 2023)
The biological removal of the two elements copper and cobalt was studied in this paper. Chlorella vulgaris (C.vulgaris) algae was used for the removal process. CHU-10 medium was used to cultivation this algae. It was observed that algae has the ability to remove more copper than cobalt due to the strong affinity of the cell membrane to bind to copper and increase the process of adsorption of this element. It was concluded that there is a good benefit to using algae in removing copper and cobalt from polluted water.
Keywords: Bioremoval, Chlorella vulgaris, copper and cobalt,elements,adsorption